Peran TRAFFIC dalam Melakukan Perlawanan terhadap Kasus Penyelundupan Cula Badak Afrika dari Afrika Selatan ke Vietnam - Adhicahya, Adam Maulana; Wahyudi, Fendy Eko; Basith Dir, Andi Akhmad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This research’s goal is to understand how TRAFFIC’s role as an NGO in the fight againtrhino horns smuggling from South Africa in Vietnam. TRAFFIC was present in Vietnamto assist the Vietnam Government in overcoming the rhino horns smuggling, whichVietnam become the highest contributor to the end of the journey of rhino horn smugglingfrom South Africa. As an NGO, what TRAFFIC do is to advise the government and makean approach to the community itself that in the end the expected output is the people andthe Vietnam Government able to solve the problem. In analyzing the role of TRAFFIC, theresearch use the concept of the role of NGO. The result of this study explains TRAFFIC’srole in Vietnam based on definition of role of an NGO by David Lewis.